James A. Garfield papers - Garfield, James A. (James Abram), 1831-1881.; Stanley-Brown, Mary Garfield, 1867-1947.
Family, personal, and official correspondence including records of Garfield's Civil War military service, diary (1848-1881), speeches and other public statements, legal papers, genealogical material, college notebooks, tributes, printed matter, scrapbooks, and other material relating primarily to Garfield's career and death. Subjects include Ohio and national politics, the disputed election of 1876, tariff and national finance, Credit Mobilier of America, and the Fitz-John Porter court-martial. Other topics include education, Hiram College, the Disciples of Christ, and the Salish (Flathead) Indians. Also includes diaries, account book, and other papers (1881-1889) of Garfield's daughter, Mary Garfield Stanley-Brown ("Mollie"). Correspondents include Chester Alan Arthur, Harmon Austin, Jeremiah S. Black, J. M. Bundy, Alexander Campbell, William E. Chandler, Julius Orrin Converse, Jacob D. Cox, John Jay Curtis, Madeleine V. Dahlgren, Ulysses S. Grant, Mark Hopkins, William Dean Howells, Robert Green Ingersoll, Francis Lieber, Thomas M. Nichol, Thomas Wharton Phillips, Albert M. Pratt, Whitelaw Reid, James H. Rhodes, A. G. Riddle, James S. Robinson, John P. Robison, William S. Rosecrans, John Sherman, Platt Rogers Spencer, and Samuel Ward.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. president, army officer, lawyer, and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Index published by the Library of Congress in 1973 available in the Library of Congress Manuscript Reading Room and on Internet. Cataloged in record 73009594.
Keywords: Arthur, Chester Alan, -- 1829-1886 -- Correspondence; Austin, Harmon, -- 1817-1893 -- Correspondence; Black, Jeremiah S. -- 1810-1883 -- Correspondence; Bundy, J. M. -- 1835-1891 -- Correspondence; Campbell, Alexander, -- 1788-1866 -- Correspondence; Chandler, William E. -- 1835-1917 -- Correspondence; Converse, Julius Orrin, -- 1834- -- Correspondence; Cox, Jacob D. -- 1828-1900 -- Correspondence; Curtis, John Jay, -- 1857-1931 -- Correspondence; Dahlgren, Madeleine Vinton, -- 1825-1898 -- Correspondence; Garfield, James A. -- 1831-1881 -- Assassination; Grant, Ulysses S. -- 1822-1885 -- Correspondence; Hopkins, Mark, -- 1802-1887 -- Correspondence; Howells, William Cooper, -- 1807-1894 -- Correspondence; Howells, William Dean, -- 1837-1920 -- Correspondence; Ingersoll, Robert Green, -- 1833-1899 -- Correspondence; Lieber, Francis, -- 1800-1872 -- Correspondence; Nichol, Thomas M. -- Correspondence; Porter, Fitz-John, -- 1822-1901.; Pratt, Albert M. -- Correspondence; Phillips, Thomas Wharton, -- 1835-1912 -- Correspondence; Reid, Whitelaw, -- 1837-1912 -- Correspondence; Rhodes, James H. -- Correspondence; Riddle, A. G. -- 1816-1902 -- Correspondence; Robinson, James S. -- Correspondence; Robison, John P., -- 1811-1889 -- Correspondence; Rosecrans, William S. -- 1819-1898 -- Correspondence; Sherman, John, -- 1823-1900 -- Correspondence; Spencer, Platt R. -- (Platt Rogers), -- Correspondence; Ward, Samuel, -- 1814-1884 -- Correspondence; Credit Mobilier of America; Hiram College; Courts-martial and courts of inquiry; Disciples of Christ; Education; Finance, Public -- United States -- History -- 1875-1901.; Presidents -- United States -- Election -- 1876.; Salish Indians; Tariff -- United States; Universities and colleges -- Ohio; Ohio -- Politics and government; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 19th century; United States -- Politics and government -- 1881-1885.; Army officers; Presidents -- United States